Understanding defiant identities: an ethnography of gays and lesbians in Harare, Zimbabwe - Muparamoto, Nelson (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
Over the years, western and local media have mediated a narrative of a thoroughly homophobic Zimbabwe, not the least emanating from the former president Robert Mugabe's ongoing homocritical utterances which recurrently generated global news stories. The country does indeed have a protracted history characterised by various forms of attacks on Gays and Lesbians of Zimbabwe, its membership, and the general lesbian, gay, bisexual, and transgender (LGBT) community. A dominant discourse has framed homosexual identities as on or beyond the border of what is acceptable, giving the clear message that they should not be tolerated. However, the narrative needs a more nuanced analysis than what has been popularised. That homophobia has played a significant role in Zimbabwe is of great import, but it is not and cannot be all there is to say about LGBT lives in the country. And, while scholarship on Zimbabwean homosexualities has engaged with debates about its indigeneity, morality and acceptability, it has as of yet not significantly explored the lived realities of non-heterosexual individuals from their own point of view. This thesis aims to begin doing exactly that, addressing the experiences of same-sex loving and attracted individuals in Harare. Drawing on ethnographic sociology, the thesis focuses on understanding how gay and lesbian identities are constructed, negotiated and experienced within an environment that is in many ways overtly homophobic, where, for example, the risk for social exclusion is considerable. It explores what characterises and shapes gay and lesbian identities in Harare in an attempt to interrogate how they reinforce, modify and challenge dominant social categories and relate to globally circulating queer identity categories. The thesis demonstrates that the construction of identities among same sex loving people in Harare variously draws on both locally and globally circulating ideas and insights. The thesis reveals that beyond the considerable attacks on homosexual identities in Zimbabwe, the intersection of local and international discourses on gay and lesbian identities produces identities that are to varying degrees emergent, fluid and perhaps fragmented. Despite attempts to expunge non-heterosexuals from Zimbabwean citizenry by drawing borders on the basis of sexual orientation, same sex loving individuals in Harare have defiantly expressed, negotiated and managed their sexual identities. The thesis describes and analyses things like dating patterns, decision making in same sex relations as well as family and religious experiences. Invoking Goffman's concept of self-presentation enables one to understand how participants expressed themselves in the midst of like-minded or homo-tolerant individuals and how they deployed themselves in 'spaces' considered homocritical or where resentment was likely to be provoked by them openly expressing their sexual orientation. Crucially, same-sex loving and attracted individuals are agentic individuals who have variously stretched the traditional meanings associated with gender and sexuality in a context characterised by heteronormativity. This thesis usefully deploys Giddens' (1991, 1992) theorisation of late modernity as characterised by conditions allowing a profusion of competing and sometimes contradictory identity discourses which offers the opportunity for self-reflexivity and identity negotiation. This helps us to understand the defiant identities. Whereas western circulating identity politics tout 'coming out of the closet', for most of the participants overt indiscriminate disclosure was to be avoided with participants therein deploying strategies that would help them to remain closeted to some family members as well as in religious circles. The consequences of 'outing' or disclosure are ostensibly not straightforward but complex, thus requiring a nuanced analysis that goes beyond the binary categories framed as either negative or positive. The thesis shows that experiences of same sex loving people in their families are complex rather than simply situated on the polar ends of either rejection or acceptance. Whilst dominant discourse has depicted religion as fuelling homophobia as it depicts a Christian identity and queer identities as incompatible, the thesis also explores how some participants challenge the borders drawn in religious circles and maintain a relatively active religious life but not always without conflict.
Keywords: Gays -- Zimbabwe; Gays -- Abuse of -- Zimbabwe; Homosexuality -- Zimbabwe; Homosexuality -- Political aspects -- Zimbabwe; Homosexuality -- Social aspects -- Zimbabwe; Homosexuality -- Religious aspects -- Zimbabwe; Homophobia -- Zimbabwe